Spatiotemporal variation in the sign and magnitude of ecosystem engineer effects on lake ecosystem production - Joseph S. Phillips; Amanda R. McCormick; Árni Einarsson; Shannon N. Grover; Anthony R. Ives (Ecosphere, 2019)
Abstract Ecosystem engineers can have diverse and conflicting effects on their ecosystems, and the balance between these effects can depend on the physical environment. This context dependence means that environmental variation can produce large differences in engineer effects through space and time. Here, we explore how local variability in environmental conditions can lead to large spatiotemporal variation in the effect of tube‐building midges on benthic ecosystem metabolism in a shallow subarctic lake. Using field experiments, we found that midge engineering increases both gross primary production (GPP) and respiration (RESP) in the sediment. Gross primary production and RESP have opposing influences on net ecosystem production, and the net effect of midges on the benthic ecosystem depends on the balance between their effects on GPP and RESP. Variation in light mediates this balance—under high light conditions, primary producers are able to exploit the structural benefits provided by midges, while in the dark, the elevation of respiration from midge engineering predominates. Benthic light levels vary spatially and temporally due to episodic cyanobacterial blooms that prevent almost all light from reaching the benthos. By quantifying the nonlinear relationship between midge engineering and light, we were able to project ecosystem‐wide consequences of natural variation in light conditions across the lake. Our results illustrate how the sign and magnitude of ecosystem‐wide effects of ecosystem engineers can vary through space and time.